Membangun Akhlakul Karimah Melalui Kegiatan Pimpinan Cabang Aisyiyah Klangenan - Machsunah, Uun; Manshur, Muhammad Iqbal; Fitri Agasya, Hesti Nauly; Nilamcaya, Mus (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of this research describes the planning and implementation of the activities of Aisyiyah Branch Klangenan Cirebon and any factors that influence its activities. This research uses a qualitative descriptive approach. Data collection using observations, interviews, and documentation. The author uses field research, gathering data at the site of the research, while data analysis techniques using explanatory preparation include data collection, data analysis, conclusions and reports. The research informants are the Deputy Chairman of Aisyiyah Klangenan Branch, Tabligh Assembly Speaker, Economic Assemblies Speaker and Education Assembles Speaker for the period 2024-2027. Temuan penelitian menunjukkan bahwa program-program Aisyiyah Klangenan yang saat ini sedang berjalan merupakan lanjutan dari program-program sebelumnya mengikuti dinamika yang ada disesuikan dengan kebutuhan warga Klangenan dan konsisten dijalankan oleh pengurusnya, untuk membangun akhlakul karimah dengan implementasi program yaitu (1) Majelis Pendidikan: Program Pendidikan Taman Kanak-kanak (Busthanul Athfal) (2) Majelis Ekonomi: Membuat pelatihan aneka kue bolu dan kuliner, koperasi simpan pinjam, arisan sembako, mengikuti lomba gizi untuk anak usia dini yang diselenggarakan oleh Pimpinan Daerah Aisyiyah Cirebon, (2)Majelis Pembinaan Kader: Pengurus Harian Aisyiyah dan anggota serta simpatisan (warga/masyarakat) rutin mendapatkan materi kajian keislamanan terutama yang berbasis fiqhunnissa (fikih untuk wanita) dan pemulasaran jenazah, (3) Majelis Tablig: Memberikan tutorial/pelatihan public speaking dan lomba pidato. This Assembly, in collaboration with the Kader Buildings Assemblies, is always included if there are activities related to framing and tablig (dakwah) organized either at the branch level, branch, district, region, or in the dream of the Muhammadiyah center, (4) the Arts, Culture, and Sports assembly: organizing routine exercises every Sunday morning. Once a month following the sports activities organized by the PDA district of Cirebon. At the specified times, this assembly will take part in any competition related to art, culture, and sports in the territory of III Cirebon.